EXPLORATION OF FAMILY-CENTERED APPROACH TO EARLY INTERVENTION: PERCEPTIONS OF EARLY INTERVENTION PROFESSIONALS - VanBuskirk, Kaylabeth Gudac (East Carolina University, 2017)
The purpose of the present research study was to gain a better understanding of the framework of Family Centered Practice (FCP) in Early Intervention (EI). FCP is considered best practice in EI service delivery. Due to the lack of empirical research regarding FCP in EI, the current research study surveyed participants’ perception of FCP in EI. Participants (N=53) were employees throughout sixteen Children’s Developmental Services Agencies (CDSA) in the state of North Carolina. Participants completed a modified version of the Family-Centered Care Self-Assessment Tool (FCC-SAT). Consistent with former research, results highlight that EI professionals perceive that their own work is family-centered. Since EI is mandated by federal law, findings underscore the importance of FCP in this field, not only in North Carolina, but throughout the United States.
Keywords: family-centered practice; early intervention; perception; service coordination